Carboxiterminal pro-endothelin-1 as an endothelial cell biomarker in thrombotic thrombocytopenic purpura - Mikes, Bálint; Sinkovits, György; Farkas, Péter; Csuka, Dorottya; Rázsó, Katalin; Réti, Marienn; Radványi, Gáspár; Demeter, Judit; Prohászka, Zoltán (Thrombosis and Haemostasis, 2016)
Thrombotic thrombocytopenic purpura (TTP) is characterised by the deficiency of the von Willebrand factor (VWF) cleaving protease (ADAMTS-13). Although several observations indicate an important role of endothelial activation in the pathogenesis of TTP, no reliable endothelial activation markers are available in the clinical management of TTP. Our aim was to investigate the presence of endothelial activation in TTP and to determine its connections with disease activity, therapy and complement activation. We enrolled 54 patients (median age 40.5; 44 females) and 57 healthy controls (median age 34; 30 females),VWF antigen, carboxiterminal-pro-endothelin-1 (CT-proET-1), complement Factor H and complement activation products (C3bBbP and SC5b-9) were measured. In both the acute and remission phase of TTP we found increased CT-proET-1 and VWF levels, while Factor H levels decreased compared with healthy controls. In remission, however, the elevated CT-proET-1 levels showed 22 % decrease when compared with the acute phase in paired samples (p=0.0031), whereas no changes for VWF and Factor H levels were observed. We also found positive correlations between CT-proET-1 levels and alternative pathway activation markers (C3bBbP; p=0.0360; r=0.4299). The data we present here demonstrate a role of endothelium activation in patients with acute TTP. The finding that CT-proET-1 levels decreased in remission compared with the acute phase further supports endothelial involvement. In addition, we show that endothelial activation also correlated with the activation of the alternative complement pathway. The data suggest that complement and endothelium activation jointly contribute to the development of TTP episodes in patients with predisposition to TTP.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: TTP; endothelial cell; endothelin-1; ADAMTS13 deficiency; complement activation